2010
DOI: 10.1007/s10554-010-9636-x
|View full text |Cite
|
Sign up to set email alerts
|

“We have a tenant” a right atrial thrombus related to a central catheter

Abstract: Hemodialysis tunneled catheter are in constant motion due to the movement of the heart. For that reason catheter tip may cause damage to the wall of the vessel or the atrium, resulting in mural thrombus formation at the point of contact. We report the case of a 36 year old asymptomatic woman with a previous chronic vascular hemodialysis catheter who was referred for routine echocardiogram before kidney transplantation. An ovoid mass compatible with thrombus was present in the right atrium. We review literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Our search produced a total of eight case series encompassing 32 cases and 32 additional individual case reports. 746 Same-patient CRAT recurrences were described in five reports 9,13,14,19,24 for a total of 68 cases of CRAT among 63 patients. Table 1 provides demographic details.…”
Section: Resultsmentioning
confidence: 98%
“…Our search produced a total of eight case series encompassing 32 cases and 32 additional individual case reports. 746 Same-patient CRAT recurrences were described in five reports 9,13,14,19,24 for a total of 68 cases of CRAT among 63 patients. Table 1 provides demographic details.…”
Section: Resultsmentioning
confidence: 98%
“…Subsequent echocardiographic identification of the catheter-attached fibrin-thrombin-cellular matrix or biomass is so common as to be considered generally benign. It is reported that portions of the fibrinthrombin biomass may remain adherent to the catheter or conversely may be sheared off and even remain in the venous system at the time of catheter removal through the skin [24][25][26]. As they are often identified in the subclavian veins, right atrium, superior vena cava (SVC) or right ventricle (RV), a knowledgeable echocardiographer will infer their presence and related etiology to a current or recently removed catheter [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Acute and complete obstruction of the SVC is caused more often by thrombosis than by compression or infiltration by a tumor ( 2 ). Risk factors for the formation of thrombus in the SVC include a hypercoagulable state in patients with malignancy, damage to the intima of the SVC from central venous catheters, and venous stasis from extraluminal compression ( 3 , 4 ). The most common causes are bronchogenic carcinoma (small-cell lung cancer and [less frequently] NSCLC) ( 5 ) and lymphoma.…”
Section: Discussionmentioning
confidence: 99%